A cross-sectional study on the prevalence and determinants of various neonatal dermatoses - Sabiha Quazi; Sanjiv Choudhary; Adarshlata Singh; Bhushan Madke; Khalid Khan; Sudhir Singh (Journal of Family Medicine and Primary Care)
Background: During the neonatal life cycle, various dermatological conditions are common. In comparison to the skin of adults, neonates' skins are more susceptible to infections in the first week of their lives. These infections often lead to many dermatological skin complications and create worrisome among parents. Hence, it is crucial to diagnose and manage such affected neonates at the earliest. This study aimed to highlight and estimate the occurrence of numerous dermatoses and assess various skin changes that occurred physiologically and pathologically in neonates. Methodology: In this cross-sectional observational study, 474 neonates were enrolled in the neonatal intensive care unit. The whole newborn skin surface, comprising the palms and soles, scalp, mucous membranes, genitalia, hair, and nails, was scrutinized under adequate light, and all changes that occurred over the skin were observed and recorded. The sample size estimation was undertaken from the references that have the least prevalent cutaneous dermatosis: hypertrichosis desquamation and napkin dermatosis. A statistical analysis like the Chi-square test was performed to associate the type of dermatosis with the parameters of age, gender, delivery type, and birth weight. Results: Of the total 474 cases, 90 (18.98%) had single dermatosis, while the remaining 384 (81.01%) had more than one form of dermatosis. Among the 384 cases, sebaceous gland hyperplasia (SGH) in 105 (22.15%), Epstein pearls in 50 (10.54%), erythema toxicum neonatorum (ETN) in 40 (8.43%), physiological desquamation in 25 (5.27%), lanugo hair in 20 (4.21%), miliaria in 22 (4.64%), salmon patch in 13 (2.74%), cradle cap/seborrheic dermatitis in 6 (1.26%), vernix caseosa in 12 (2.53%), transient neonatal pustular melanosis in 13 (2.74%), congenital melanocytic nevus in 20 (4.21%), hemangioma in 15 (3.16%), neonatal acne in 5 (1.05%), napkin dermatitis in 10 (2.10%), cutis marmorata in 6 (1.26%), milia in 2 (0.42%) intertrigo 3 (0.63%), collodion baby in 2 (0.42%), and neonatal occipital alopecia in 2 (0.42%) neonates each and others, respectively. Conclusion: The findings from the present study were representative of a specific racial/geographic distribution and will assist in adding or comparing the prevalence of neonatal dermatosis with other geographic regions as the array of dermatological characterizations in neonates varies as per time and place. This study aims to provide insight into the future implications in the neonatal dermatology domain and avoid further skin complications.